Introduction of threat analysis into the land-use planning process - KONTIC, Davor; KONTIC, Branko (Journal of hazardous materials, 2009)
The subject of this paper is a method for introducing risk assessment into the land-use planning (LUP) process. Due to adaptations of the results of risk assessment, which are needed to make the risk assessment usable by land-use planners, we term the overall process threat analysis. The key features of the threat analysis can be summarised as follows. (i) It consists of three main steps. The first is determination of the threat intensity level of an accident, the second is analysis of the environmental vulnerability of the surroundings of an accident, and the third, integrating the previous two, is determination of a threat index in the accident impact zone. All three are presented in GIS based maps, since this is a common expression in LUP. (ii) It can and should be applied in the early stages of the LUP process. The methodology is illustrated by an example in the context of renewal of a land-use plan for the Municipality of Koper in Slovenia. The approach of threat analysis follows directions of the Article 12 of the Directive 96/82/EC of the European Commission (the Seveso II Directive).